(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the past 25 years, the Indian economy has undergone revolutionary transformations in relation to its political system. Some of these changes are progressive and beneficial to the country and society, nevertheless. A few new aspects of Indian politics that don’t seem to be fully democratic have emerged at the advent of the twenty-first century. These characteristics don’t indicate totalitarianism or a dictatorship;